Refractory dermatomyositis and polymyositis in adults: Treatment options - Guerrero-Oviedo, María Camila (2023)
Dermatomyositis and polymyositis are rare autoimmune diseases, classified as inflammatory myopathies, clinically characterized by muscle weakness, frequently accompanied by extramuscular manifestations. Patients usually achieve remission or low levels of disease activity with initial treatment with glucocorticoids (may or may not be combined with immunomodulators), when this fails, it is considered refractory dermatomyositis and polymyositis (a new muscle biopsy must first be performed to rule out alternative diagnoses), thus additional treatments will be required for its management. The treatment of refractory dermatomyositis and polymyositis continues to be a challenge due to the lack of scientific evidence to validate the effectiveness of alternative drugs. This review presents some of the therapeutic alternatives. Biological therapies, especially rituximab and abatacept, were found in the literature as promising to reduce morbidity and mortality in both pathologies.